Modulus τ linking leptonic CP violation to baryon asymmetry in A 4 modular invariant flavor model - Hiroshi Okada; Yusuke Shimizu; Morimitsu Tanimoto; Takahiro Yoshida (Journal of High Energy Physics, 2021)
Abstract We propose an A 4 modular invariant flavor model of leptons, in which both CP and modular symmetries are broken spontaneously by the vacuum expectation value of the modulus τ. The value of the modulus τ is restricted by the observed lepton mixing angles and lepton masses for the normal hierarchy of neutrino masses. The predictive Dirac CP phase δ CP is in the ranges [0°, 50°], [170°, 175°] and [280°, 360°] for Re [τ] < 0, and [0°, 80°], [185°, 190°] and [310°, 360°] for Re [τ] > 0. The sum of three neutrino masses is predicted in [60, 84] meV, and the effective mass for the 0νββ decay is in [0.003, 3] meV. The modulus τ links the Dirac CP phase to the cosmological baryon asymmetry (BAU) via the leptogenesis. Due to the strong wash-out effect, the predictive baryon asymmetry Y B can be at most the same order of the observed value. Then, the lightest right-handed neutrino mass is restricted in the range of M 1 = [1.5, 6.5] × 1013 GeV. We find the correlation between the predictive Y B and the Dirac CP phase δ CP . Only two predictive δ CP ranges, [5°, 40°] (Re [τ] > 0) and [320°, 355°] (Re [τ] < 0) are consistent with the BAU.